Lembaga Pendidikan Islam Dalam Lintasan Sejarah di Indonesia (Kajian Historis Perkembangan Lembaga Pendidikan Islam) - Hidra Ariza (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Abstract The rapid development of Islam in Indonesia since its inception until now, cannot be separated from the role of Islamic educational institutions. When viewed from the early entry of Islam into Indonesia, Islamic educational institutions experienced several changes in name and form, which were the result of changes in the social conditions of society and developments in science and technology. Starting from Islamic education which is still patterned as Hindu education to the establishment of technology-based Islamic education institutions at this time. Among the classical Islamic educational institutions that still exist today include surau, pesantren, meunasah, Islamic tertiary institutions, etc. There are some Islamic educational institutions whose existence is no longer found, some are still standing but have experienced a decline in function, some have managed to survive by adapting to the demands of the times. One of the classical Islamic educational institutions that is able to develop according to the times is the pesantren. Evidenced by the existence of Islamic boarding schools with various special sciences that are integrated with the values of Islamic education. This article was written using the library research method which utilizes various scientific literature to obtain the necessary data. AbstrakPesatnya perkembangan Islam di Indonesia sejak awal masuknya hingga saat ini, tidak terlepas dari peran lembaga pendidikan Islam. Jika dilihat dari awal masuknya Islam ke Indonesia, lembaga pendidikan Islam mengalami beberapa perubahan nama dan bentuk, yang merupakan akibat dari perubahan keadaan social masyarakat serta perkembangan ilmu pengetahuan dan teknologi. Mulai dari pendidikan Islam yang masih bercorak pendidikan Hindu hingga berdirinya lembaga pendidikan Islam yang berbasis teknologi pada saat ini. Diantara lembaga pendidikan Islam klasik yang masih eksis bertahan hingga saat ini diantaranya adalah surau, pesantren, meunasah, perguruan tinggi Islam, dll. Ada sebagian lembaga pendidikan Islam yang sudah tidak ditemui lagi eksistensinya, ada yang masih berdiri namun mengalami penurunan fungsi, ada yang berhasil bertahan dengan menyesuaikan tuntutan zaman. Salah satu lembaga pendidikan Islam klasik yang mampu berkembang sesuai dengan perkembangan zaman adalah pesantren. Terbukti dengan adanya pesantren dengan berbagai keilmuan khusus yang diintegrasikan dengan nilai-nilai pendidikan Islam. Artikel ini ditulis dengan memakai metode library research yang memanfaatkan berbagai literatur ilmiah untuk mendapatkan data yang diperlukan.